Multilevel drivers of human immunodeficiency virus/acquired immune deficiency syndrome among black philadelphians: exploration using community ethnography and geographic information systems. - Brawner, Bridgette M; Reason, Janaiya L; Goodman, Bridget A; Schensul, Jean J; Guthrie, Barbara (Nursing research, 2015)
Unequal human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) distribution is influenced by certain social and structural contexts that facilitate HIV transmission and concentrate HIV in disease epicenters. Thus, one of the first steps in designing effective community-level HIV/AIDS initiatives is to disentangle the influence of individual, social, and structural factors on HIV risk. Combining ethnographic methodology with geographic information systems mapping can allow for a complex exploration of multilevel factors within communities that facilitate HIV transmission in highly affected areas.